Curing modes affects micro-tensile bond strength and durability of dual curing resin cements to dentin - Li, Zimeng; Yan, Xiaoyuan; Toufani, Negin; Sano, Hidehiko; Fu, Jiale (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundTo evaluate the effects of curing modes on the micro-tensile bond strength and durability of 6 different dual curing resin cements to dentin.Methods84 human molars were divided into 7 groups (n = 12), and were further distributed into two subgroups according to the two curing modes: light-curing (L) and self-curing (D) (n = 6). The 6 dual-cured resin cements were: DU (Duolink, Bisco), TC (TheraCem, Bisco), MS (Multilink Speed, Ivoclar), N3 (Nexus 3 Universal, Kerr), R2 (RelyX U200, 3M) and RU (RelyX Ultimate, 3M). The universal adhesives were: All Bond Universal (Bisco); Adhesive Universal Vivapen (Ivoclar); Optibond Versa Adhesive (Kerr); Scotch Bond Universal Adhesive (3M). RU was placed directly on processed adhesive layer without light-curing, set as group 7. Micro-tensile bond strength test was carried out after 37°C water storage for 24 h, 3 months and 6 months, respectively. Three-way ANOVA and Games-Howell test were performed by SPSS 19.0 (α = 0.05).ResultsThe Three-way ANOVA indicated that bonding performance was significantly affected by curing mode (p = 0.000, F = 1,237.510), resin cement (p = 0.000, F = 59.507) and storage time (p = 0.000, F = 97.888). The interaction of these three factors was significant (p = 0.017, F = 2.071).ConclusionThe bonding strength and durability of dual curing resin cements were significantly improved by light-curing process. In addition, the bonding strength of resin cements with different experimental condition was material depended. Among all tested resin cements, N3 exhibits the most favorable outcomes.Clinical RelevanceA dual curing procedure is recommended in clinical application. Among all tested resin cements, N3 exhibits the most favorable outcomes.